Temporal Bone Pneumatization: Relationship With Sex and Variants of the Ethmoid and Sphenoid Bone. Issue 8 (7th November 2021) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Panzeri, Marta; Termine, Giovanni; Floridi, Chiara; Sforza, Chiarella
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Pneumatization variants of the temporal bone have a crucial importance in several surgical interventions. However, very few data are known about possible correlation with other pneumatization variants. Pneumatization of glenoid fossa, petrous apex, and infralabyrinthine portion of temporal bone was assessed in 200 computed tomography scans, equally divided between males and females (18–92 years). Pneumatization variants of the ethmoid (concha bullosa, agger nasi, pneumatized crista galli) and the sphenoid sinuses (pneumatized pterygoid processes, anterior clinoid processes, dorsum sellae, volume) were recorded as well. Differences in prevalence of each pneumatization type according to sex and side, among different portions of the temporal bone, and between temporal bone and the pneumatized variants of the ethmoid bone and sphenoid sinuses, were assessed through chi-square test ( P  < 0.05). Differences in sphenoid volume among different pneumatization degrees of the temporal bone were assessed through 1-way analysis of covariance test ( P  < 0.05). Pneumatization of the petrous apex and the infralabyrinthine portion was significantly more frequent in males than in females, whereas pneumatization of the glenoid fossa was more often observed on the right side ( P  < 0.05). Variants of the temporal bone are all related one with each other in males, whereas in females only the relationship between pneumatized petrous apex and infralabyrinthine portion was found. Moreover, in females the pneumatized petrous apex was related with pneumatized anterior clinoid process, and the pneumatized infralabyrinthine portion was related with the sphenoid sinus volume. Results may be useful for predicting these important variants in planning surgical interventions of the cranial base.